'Letting them eat cake': Narrative templates in current affairs/news journalism - John Carr (Asia Pacific Network, 2009)
This article explores the role of narrative templates in a core domain of public communication, describing a series of narrative structural patterns that underlie the scripting of news and current affairs ‘reports’. From an initial account of the nature of narrative templates and their relation to audience expectations and interpretative regimens, a number of  specific story-styles that are employed recurringly in news programmes are described, examining their use and impact for capturing and maintaining audience attention. The process of telling the audience the stories it wants to hear is critiqued in terms of the capacity to subvert the quality of public communication and in terms of enduring concerns within discursive theory.